Gestão de custo hospitalar: estudo de casos no município de São Paulo - Arashiro, Leila Akemi (2004)
This dissertation explores organizational characteristics that operate as critical conditions to the implementation of cost management in hospitals. It addresses how certain internal conditions to the organizations affect the process of implementation, administration and utilization of costing systems as effective supporting tools to the decision making in the hospital sector management. Based on the results of two case studies from the municipality of Sao Paulo, it points out that both in the private and in the public sectors, the successful implementation of cost management in hospitals appeared to be conditioned to specific characteristics related to the commitment of managers with the process of costing system implementation, the dynamics of the information flow and the use of technology information systems.